Exercise Interventions on Balance in Older People: a Systematic Review - Brandão Loureiro, Vânia Azevedo Ferreira; Paixão, Carlos; Castillo-Viera, Estefania (Arena-Journal of Physical Activities, 2021)
Introduction: Age-related changes in the sensorimotor and neuromuscular system negatively affect performance in static and dynamic postural control even in healthy older adults, leading to deficits in balance and gait performance with negatively impact on the functional ability of the older person. Regular exercise can elicit many favourable responses that contribute to balance improvement. Objectives: The objective of this systematic review is to present evidence for effectiveness of exercise interventions designed to improve balance in healthy older people. Methods: The studies were identified from four databases (PubMed, Web of Science, Cochrane Library and Sportdiscus) from January 2011 to January 2020. A total of 17 articles meet the inclusion criteria. Results: Statistically significant effects were reported for static and dynamic balance, translated into several balance abilities improve-ments. The most used type of exercise was the gait, balance and functional training, followed by the strength/resistance training. There is a lack of consensus regarding to balance programs methodology. Conclusion: Exercise appears to have beneficial effects on balance ability. We considered fundamental that the studies should include the specifications of the intervention program regarding to intensity control, exercises performed, guidelines used in the balance exercises and the exercise progression and variation during training. This information will help instructors to provided validated routine exercises.